1999
DOI: 10.1074/jbc.274.19.13666
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Saccharomyces cerevisiae Prion-like Protein Ure2

Abstract: Sacchromyces cerevisiae prion-like protein Ure2 was expressed in Escherichia coli and was purified to homogeneity. We show here that Ure2p is a soluble protein that can assemble into fibers that are similar to the fibers observed in the case of PrP in its scrapie prion filaments form or that form on Sup35 self-assembly. Ure2p self-assembly is a cooperative process where one can distinguish a lag phase followed by an elongation phase preceding a plateau. A combination of size exclusion chromatography, sedimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
194
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(207 citation statements)
references
References 38 publications
12
194
1
Order By: Relevance
“…In the case of Ure2, to obtain ideal results in this two-way experiment requires a careful balance of pH, temperature, protein concentration and choice of buffer [27]. The conditions found to be 'ideal' for folding experiments (Tris-HCl buffer pH 8.4, 0.2 M NaCl, 25°C and 1 μM protein concentration) unsurprisingly resemble the conditions adopted for Ure2 purification in a variety of labs [26,27,32,109], and coincide with maximal stabilization of the native state of Ure2 with respect to partially-folded intermediates [36]. Nevertheless, under these conditions, the folding kinetics of Ure2 is extremely complex and a variety of folding intermediates are transiently populated during unfolding or refolding [27,35,36].…”
Section: Comparison Of Different Denaturation Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the case of Ure2, to obtain ideal results in this two-way experiment requires a careful balance of pH, temperature, protein concentration and choice of buffer [27]. The conditions found to be 'ideal' for folding experiments (Tris-HCl buffer pH 8.4, 0.2 M NaCl, 25°C and 1 μM protein concentration) unsurprisingly resemble the conditions adopted for Ure2 purification in a variety of labs [26,27,32,109], and coincide with maximal stabilization of the native state of Ure2 with respect to partially-folded intermediates [36]. Nevertheless, under these conditions, the folding kinetics of Ure2 is extremely complex and a variety of folding intermediates are transiently populated during unfolding or refolding [27,35,36].…”
Section: Comparison Of Different Denaturation Methodsmentioning
confidence: 99%
“…Subsequent biophysical analysis of the purified Ure2 protein has shown that the structural properties of the N-terminal and C-terminal regions are also distinct. The N-terminal domain is extremely sensitive to protease digestion [26][27][28]104] and progressive deletion of the N-terminal domain has no effect on the dimerisation, stability or folding kinetics of the protein in vitro [27,33,35,36,105] (see Fig. 6).…”
Section: Role Of the N-terminal Prion Domain In Ure2 Structure And Fomentioning
confidence: 99%
See 1 more Smart Citation
“…The assembly reaction follows a nucleationgrowth mechanism with a lag phase that can be eliminated by the addition of minute amounts of preformed fibrils to a solution of native soluble Ure2p (11). The assembly reaction of native full-length Ure2p into fibrils under physiologically relevant conditions is believed to be at the origin of the [URE3] phenotype in the yeast.…”
mentioning
confidence: 99%
“…Native soluble Ure2p assembles in vitro into fibrils that exhibit the characteristics of amyloids in that they are about 20 nm wide and more than 1 m long, bind thioflavin T and Congo Red, show yellow-green birefringence in polarized light upon Congo Red binding, and exhibit an increased resistance to proteolysis (11)(12)(13). The assembly reaction follows a nucleationgrowth mechanism with a lag phase that can be eliminated by the addition of minute amounts of preformed fibrils to a solution of native soluble Ure2p (11).…”
mentioning
confidence: 99%